2022
DOI: 10.3390/s22155599
|View full text |Cite
|
Sign up to set email alerts
|

Automatically Annotated Dataset of a Ground Mobile Robot in Natural Environments via Gazebo Simulations

Abstract: This paper presents a new synthetic dataset obtained from Gazebo simulations of an Unmanned Ground Vehicle (UGV) moving on different natural environments. To this end, a Husky mobile robot equipped with a tridimensional (3D) Light Detection and Ranging (LiDAR) sensor, a stereo camera, a Global Navigation Satellite System (GNSS) receiver, an Inertial Measurement Unit (IMU) and wheel tachometers has followed several paths using the Robot Operating System (ROS). Both points from LiDAR scans and pixels from camera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…Nevertheless, finding suitable data to train these algorithms is not always easy, as they usually require manual tagging, which is a slow and error-prone process. To overcome this problem, synthetic datasets have been published, where data is directly acquired from a robotic simulator [ 26 ], making it free of labeling errors and reducing human labor.…”
Section: Related Workmentioning
confidence: 99%
“…Nevertheless, finding suitable data to train these algorithms is not always easy, as they usually require manual tagging, which is a slow and error-prone process. To overcome this problem, synthetic datasets have been published, where data is directly acquired from a robotic simulator [ 26 ], making it free of labeling errors and reducing human labor.…”
Section: Related Workmentioning
confidence: 99%
“…Gazebo is an open-source 3D robotics simulator with integrated physics engine [26] that allows the development of realistic models of complex environments [25]. In this way, it has been used as a simulation environment for technological challenges [27].…”
Section: Natural Environment Modellingmentioning
confidence: 99%
“…Reliable CNN training requires a lot of images labelled pixel by pixel as input, which can be available in public datasets [21,22]. Synthetic data are a relevant alternative for training both traditional machine [23] and deep learning methods [24] because ground truth data can be labelled automatically, which avoids tedious and error-prone manual or assisted tagging [25].…”
Section: Introductionmentioning
confidence: 99%
“…In the virtual robot, a configuration is made according to the ROS protocol to enable the virtual robot to run in the Gazebo simulator [12]- [14]. In this research, the program flow is designed as shown in Fig.…”
Section: Virtual Robotmentioning
confidence: 99%